Метафоризація концепту життя в мові української поезії - Кравець Лариса Вiкторiвна (SlavVaria, 2022)
Metaphorization of the concept of life in the language of Ukrainian po-etry. The article discusses the metaphor "life" in Ukrainian poetry of the 20th - early 21st century. The source of the material was the works of Ukrainian writ-ers from mainland Ukraine and the Diaspora. Using the method of metaphori-cal modeling, the key models of the metaphors of "life" in the Ukrainian poetry of the analyzed period were identified and characterized, and individual au-thor's metaphors that were based on them were analyzed. The change of meta-phors is explained, the specificity of their meanings is described. It has been established that the metaphors recorded in the Ukrainian poetry of the XX - Art. XXI Art. reveal a different understanding of life by each writer, which is due to a complex of external and internal factors.